Atividade antibacteriana dos óleos essenciais do manjericão (Ocimum basilicum Linnaeus) e do gengibre (Zingiber officinale Roscoe) frente a linhagens de Escherichia coli enteropatogênicas isoladas de hortaliças - Martins, André Gustavo Lima de Almeida (2010)
Considering the increase of the involvement of vegetables in the transmission of microorganism include the enteropathogenic Escherichia coli multiresistance to conventional drugs, the search for new antimicrobial substances from natural sources, including the essential oils, has been intensive. This study aimed evaluate the antibacterial activity of the essential oil from basil (Ocimum basilicum Linnaeus) and ginger (Zingiber officinale Roscoe) front strains of enteropathogenic Escherichia coli isolated from grass cultivated by organic and hydroponic system, sold in street markets and supermarkets of São Luís city MA, using the Method of Diffusion in Disc (MDD). Were analyzed 100 samples of curly lettuce and 60 of watercress. In this work, carried out the extraction of the essential oils of basil (leafs) and ginger (rhizome) by steam drag along method (hydro-distillation) using a Clevenger system. Besides density, refraction rate, solubility, color and physics appearance constants, the majority compounds were identified of each essential oil by the Gas Chromatography technique docked to Masses Spectrometry (CG-MS). The results showed that, independently the cultivation system, as many the samples of lettuce as the samples of watercress presented contamination by serogroups of E. coli classical EPEC and enterohemorragic (EHEC). In the lettuces were identified the serogroups: O55, O26, O111, O114, O125, O126, O127, O142 (E. coli EPEC) e O157 (E. coli EHEC) and in the watercress, O55, O125, O126 e O127 (E. coli EPEC). About the antibacterial activity, as the essential oil of basil as the ginger one showed bactericidal action front serougrups of E. coli isolated of the lettuces and watercress.